Medically indicated late preterm delivery and its impact on perinatal morbidity and mortality: a retrospective population-based cohort study. (2nd October 2019) - Besser, Limor; Sabag-Shaviv, Liat; Yitshak-Sade, Maayan; Mastrolia, Salvatore Andrea; Landau, Danielle; Beer-Weisel, Ruthy; Klaitman, Vered; Benshalom-Tirosh, Neta; Mazor, Moshe; Erez, Offer
Abstract: Objective: In the last few decades, attention has been focused on morbidity and mortality associated with late preterm delivery (34–36 + 6/7 weeks), accounting for 60–70% of all preterm births. This study is aimed to determine (1) the prevalence of late preterm deliveries (spontaneous and medically indicated) in our population; and (2) the rate of neonatal morbidity and mortality as well as maternal complications associated with the different phenotypes of late preterm deliveries. Study design: This retrospective population-based cohort study, included 96, 176 women who had 257, 182 deliveries, occurred between 1988 and 2011, allocated into three groups: term ( n  = 242, 286), spontaneous ( n  = 10, 063), and medically indicated ( n  = 4833) late preterm deliveries. Results: (1) Medically indicated late preterm deliveries were associated with increased maternal morbidity, as well as neonatal morbidity and mortality, in comparison with other study groups ( p  < .01 for all comparisons); (2) medically indicated late preterm delivery was an independent risk factor for composite neonatal morbidity (low Apgar score at 5', seizures, asphyxia, acidosis) after adjustment for confounding factors (maternal age and ethnicity and neonatal gender) and stratification according to gestational age at delivery; and (3) the proportion of medically indicated late preterm deliveries affected the neonatal mortality rate. Below 35% of all late preterm deliveries, indicated late preterm birth were associated with a reduction in neonatal mortality; however, above this threshold medically indicated late preterm deliveries were associated with an increased risk for neonatal death. Conclusions: (1) Medically indicated late preterm deliveries were independently associated with adverse composite neonatal outcome; and (2) to benefit in term of neonatal outcome from the tool of medically indicated late preterm birth, their proportion should be kept below 35% of all late preterm deliveries, while exceeding this threshold increases the risk of neonatal mortality.